1990
DOI: 10.1159/000117320
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Sonography as a Diagnostic Tool in Vascular Dementia

Abstract: Transcranial Doppler monitoring of the flow velocity at the level of the middle cerebral artery was performed in 40 demented patients, 20 with multi-infarct dementia (MID) and 20 with senile dementia of the Alzheimer type (SDAT), and in 25 age-matched controls. The following conditions were evaluated: (1) rest; (2) 60 s hyperventilation; (3) longest possible apnea, and (4) 5 min closed-circuit air rebreathing. We also measured: Paco2 levels at rest and under stimulus conditions; mean flow velocity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 0 publications
5
37
1
Order By: Relevance
“…Blood flow reduction could indeed represent the functional correlate of a reduced arterial diameter, reflecting the presence of microangiopathy in both diseases [24], which is in accordance with previous observations [19, 20] and partially with those of Foerstl et al [25] and Biedert et al [26], who observed a significant PI increase only in the VaD group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Blood flow reduction could indeed represent the functional correlate of a reduced arterial diameter, reflecting the presence of microangiopathy in both diseases [24], which is in accordance with previous observations [19, 20] and partially with those of Foerstl et al [25] and Biedert et al [26], who observed a significant PI increase only in the VaD group.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were already reported by Provinciali et al [19], who observed reduced responses in hypocapnic conditions for both VaD and AD and, under hypercapnic conditions, only for VaD. An altered reactivity of the posterior cerebral arteries to visual stimulation was observed in VaD with respect to AD and normal controls, suggesting that the occipital cortex is partially preserved in patients with AD [33].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…6,8,9,21 Impaired cerebral autoregulation and altered pulsatility characteristics measured by TCD were found in patients with vascular dementia and lacunes [22][23][24][25] ; however, most of these studies did not distinguish between cerebral microangiopathy and lacunar and territorial brain infarction.…”
Section: Discussionmentioning
confidence: 99%